The Surveillance Database Development of Risk Factor for Dengue Fever in Mataram District Health Office - Sinawan, Sinawan; Martini, Santi; Purnomo, Windhu (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTSystem of DHF epidemiological surveillance that is currently running in Mataram District Health Office has not been able to provide information about the incidence of DHF is based on risk factors. Besides, the process of manufacturing and analysis of data were still done manually, so the level of consistency and accuracy of data was still less. This research aimed to develop database surveillance risk factor of DHF incidence. This type of research is action research. This research was conducted at the Mataram District Health Office NTB province at April 2014 until August 2014, informants in this study consists of three (3) members, namely Head of P2PB Section, DHF P2 Program Manager and Surveillance Staff. The data used are primary and secondary data. Database design includes logical and physical design. Performed on the logic design is the normalization of the data, create relationships between data illustrates the entity relationship diagram (ERD) and proceed to the physical design to create a prototype database using Epi Info software application for Windows version 3.5.1. Trial involving two (2) the informants. Evaluation trials database surveillance of risk factors DHF incidence to assess the ease, speed, accuracy and completeness of the resulting data. Results of this study is new database surveillance risk factor of DHF incidence that can be used easily, quickly and can be results more accurate information.Keywords: DHF, surveillance, risk factor, database.